2019
DOI: 10.1002/jat.3897
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive disorders in female rats after prenatal exposure to sodium arsenite

Abstract: Arsenic is a metalloid widely found in the environment in organic and inorganic forms. Exposure to inorganic arsenic forms via drinking water has been associated with an increased incidence of negative health effects, including reproductive disorders and dysfunction of the endocrine system. However, the impact of arsenic exposure on female reproductive development is still unclear. Therefore, in the present study, we evaluated the effects of prenatal exposure to arsenic on the initial sexual development and pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Further, it was also associated with delayed menarche and alteration in estrous cycle number and length. [ 80 ]…”
Section: Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Further, it was also associated with delayed menarche and alteration in estrous cycle number and length. [ 80 ]…”
Section: Pathophysiologymentioning
confidence: 99%
“…Further, it was also associated with delayed menarche and alteration in estrous cycle number and length. [80] 4.8 | Effect on muscles and As induced diabetes Histological investigations and other animal studies have demonstrated the connection between As exposure and muscle injury. [81] According to reports, exposure to As enhanced the muscular cells' resilience to fatigue and prevented the development of new muscle.…”
Section: Effect On the Reproductive Systemmentioning
confidence: 99%
“…For the male reproductive system, arsenite lowers the weight of testicular tissues and reduces the sperm counts along with the lower sperm motility, chromosomal aberrations and morphological sperm abnormalities ( Wu et al, 2020 ). As for female, arsenite causes female masculinization in rats, ultimately impairing their normal reproductive function ( Souza et al, 2020 ). In addition, arsenite delays the initiation of puberty in rats and increases the incidence of spontaneous abortion and stillbirth, accompanied with the presence of the antioxidant enzyme activity and sex hormone concentrations in the ovaries and uterus ( Quansah et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over 50 years of research has shown that maternal experiences at this stage have profound and diverse consequences, affecting the behavior of the young in relation to food selection, memory, learning, cognitive ability, psychomotor development, and temperament as well as parental, aggressive, exploratory, and sexual behaviors (Brunton 2013). Studies carried out with rats exposed to stress during pregnancy concluded that the male offspring had impaired sexual behavior, with evidence of under-masculinization in adulthood (Souza et al 2019;Hernández et al 2020). However, in rabbits, few articles on this subject matter have been published (Brunton 2013;Bánszegi et al, 2015;Simitzis et al, 2015;Benedek et al, 2020).…”
Section: Introductionmentioning
confidence: 99%